Tandem Au-Catalyzed 3,3-Rearrangement−[2 + 2] Cycloadditions of Propargylic Esters: Expeditious Access to Highly Functionalized 2,3-Indoline-Fused Cyclobutanes - Zhang, Liming (Journal of the American Chemical Society, 2005)
The treatment of readily available propargylic indole-3-acetates with a catalytic amount of AuCl(PPh3)/AgSbF6 leads to tandem activations of the propargylic esters and the in situ generated allenylic esters, resulting in expeditious access to highly functionalized cyclobutanes with fused 2,3-indoline and γ-lactone rings and an exocyclic E-double bond through sequential 3,3-rearrangement and [2 + 2] cyclization.